Informal accountability. Street-level bureaucrats' tactics to defy bad reputation in agencies of the Argentinian justice system. (2nd July 2020) - Rohrer, Ingo
ABSTRACT: This article illustrates how employees of the Argentinian Territorial Agency for Access to Justice fear being perceived as lazy bureaucrats involved in clientelist networks. In order to improve their image, they fulfil requirements for formal accountability, but use additional, informal modes of accountability to underline the agency's performance, impact and relevance. I illustrate that employees identify with the agency they are working for and are inspired in their accountability by methods that have proven to be effective in human rights movements and NGOs. Thus, my ethnographic example invites discussions in the overlapping fields of accountability and political activism.